ANALISIS FAKTOR-FAKTOR PEMBENTUK KINERJA (RGEC) PADA PERBANKAN INDONESIA: (Studi Kasus pada Bank yang Terdaftar di BEI Periode 2010-2013) - Eka Setiaji, Hanif; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to analyze the major factors that forming the performance of the banks in Indonesia based on Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) financial ratios. Variables used in this research are financial ratio that make up the RGEC model on bank performance consists of Net Performing Loan (NPL), Interest Expense Ratio (IER),Loan to Deposit ratio (LDR), Loan to Asset Ratio (LAR), and Cash Ratio(CR) as Risk Profile aspect, self-assessment bank rating is an aspect of Good Corporate Governance, Gross ProfitMargin (GPM), Gross Yield on Total Assets (GOTA), Net Interest Margin (NIM), Net ProfitMargin (NPM), Profit Margin (PM),Return on Equity (ROE), Return on Assets (ROA), Return onTotal Assets (ROTA), and Beban Operasional per Pendapatan Operasioanal (BOPO) as Earnings aspect, and then Capital Adequacy Ratio (CAR), Deposit Risk Ratio (DRR), Primary Ratio (PR), and Risk Assets Ratio (RAR) as Capital aspect.The population in this research are all banking companies listed on the Indonesian StockExchange in 2010-2013. The sampling method used in this research was purposive sampling method with the specified criteria, listed for 4 years and have no delisted during the period, whichbring out 124 sample. Data collection method used in this research is documentation study usingannual reports of each banking between 2010-2013. Factors analysis was used as a method of data analysis in this researchThe result of analysis showed that from 19 ratio, there are 18 significant ratio as formingthe ratio of bank performance, and 13 of them are the permanent factors that forming the banks performance. That thirteen ratio are PM, ROE, ROTA, ROA, NPM, BOPO, PR, RAR, CAR, DRR, NPL, CR and GCG. There is only 1 ratio which is not significant forming the Indonesian banking performance, and it’s LAR.